The Effect of a Cognitive Approach on EFL Students’ Motivation in Terms of Task-Value, Control of Learning Beliefs, and Self-efficacy - Albashtawi, Abeer; Al Awabdeh, Abdel Hameed (Dirasat: Human and Social Sciences, 2023)
This study examined the effect of the Cognitive Academic Language Learning Approach (CALLA) on the improvement of EFL students’ motivation in terms of task value, control of learning beliefs, and self-efficacy. This mixed-methods study consisted of two phases: quantitative and qualitative. In the first phase which was a quasi-experimental design with two groups (experimental and control), all students responded to a motivation questionnaire. Qualitative data were collected using focus group interviews which were done with participants in the experimental group to obtain their perceptions of the effect of the intervention programme on the improvement of the three motivational constructs. While the quantitative data were analysed using descriptive statistics, t-test, Analysis of Variance (ANCOVA), and Multivariate Analysis of Variance (MANOVA), the interviews were transcribed and analysed qualitatively. The study revealed that CALLA was effective in increasing students’ motivation in terms of task value, control of learning beliefs, and self-efficacy. Thus, CALLA can be recommended for L2 students in academic reading courses.